Devotion as a Form of Veneration for the Mother of Jesus: A Systematic Review of the Literature - Agustinus Abraham (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2026)
This study examines Marian devotion in the Catholic Church as a form of veneration (dulia) rather than worship (latria), addressing persistent misconceptions that equate Catholic devotional practices with idolatry. The research aims to identify the forms of Marian devotion practiced by Catholics in Indonesia and to analyze the challenges encountered in living out these practices. A descriptive qualitative approach was employed using a Systematic Literature Review (SLR) guided by the PRISMA framework. Two hundred articles were initially identified through Google Scholar and screened according to relevance, recency, geographical context, and methodological criteria, resulting in four eligible studies for analysis. The findings reveal four principal forms of devotion: the use of statues as aids to prayer, pilgrimages to Marian sites, Montfort-style Marian consecration, and the rosary emphasizing praise, imitation, and prayer with Mary. These practices deepen faith and lead the faithful closer to Christ without replacing divine worship. Challenges include external religious intolerance toward devotional symbols and limited theological understanding among believers. Therefore, sound catechesis grounded in Scripture and Church Tradition is essential to ensure authentic and balanced Marian devotion.